2020
DOI: 10.1186/s40854-020-00198-x
|View full text |Cite
|
Sign up to set email alerts
|

An empirical examination of investor sentiment and stock market volatility: evidence from India

Abstract: Understanding the irrational sentiments of the market participants is necessary for making good investment decisions. Despite the recent academic effort to examine the role of investors’ sentiments in market dynamics, there is a lack of consensus in delineating the structural aspect of market sentiments. This research is an attempt to address this gap. The study explores the role of irrational investors’ sentiments in determining stock market volatility. By employing monthly data on market-related implicit ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 64 publications
1
14
0
Order By: Relevance
“…Extreme volatility results in herding, especially for emerging equity markets such as Turkey (Balcilar & Demirer, 2015), Spain (Blasco et al, 2012;Pochea et al, 2017) and China (Chiang et al, 2013). The COVID-19 pandemic has engulfed financial markets with negative sentiment thereby increasing volatility (Ali et al, 2020;Chen et al, 2014;Haritha & Rishad, 2020;Naseem et al, 2021) which is the main reason for herding in the stock markets. Aslam et al (2020) argue that European markets witnessed non-rational investing and behaved like roller coasters during COVID-19 outbreak period that resulted in herding.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Extreme volatility results in herding, especially for emerging equity markets such as Turkey (Balcilar & Demirer, 2015), Spain (Blasco et al, 2012;Pochea et al, 2017) and China (Chiang et al, 2013). The COVID-19 pandemic has engulfed financial markets with negative sentiment thereby increasing volatility (Ali et al, 2020;Chen et al, 2014;Haritha & Rishad, 2020;Naseem et al, 2021) which is the main reason for herding in the stock markets. Aslam et al (2020) argue that European markets witnessed non-rational investing and behaved like roller coasters during COVID-19 outbreak period that resulted in herding.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A pandemic transmits uncertainty to the economy, increases stock investors’ fears, and induces pessimistic sentiments on expected returns. PH and Rishad ( 2020 ) argued that investors’ irrational sentiments significantly lead to excessive stock market volatility. To verify the mediating effect, investors’ fear measured in the VIX, which is a real-time market index signifying the market’s expectations on a 30-day forward-looking volatility, is introduced into the regression.…”
Section: Analysis Of Ols Regression and Empirical Resultsmentioning
confidence: 99%
“…For instance, based on 45-year long data retrieved from 362 companies across 16 European countries, Nogueira Reis and Pinho (2020) showed that monthly stock returns were significantly predicted by 13 investor sentiment indices. At the other side of the spectrum, Haritha and Rishad (2020) designed an irrational sentiment index using monthly stock market data and showed that the index triggered high market volatility. With a specific focus on the German society, Rakovská (2021) designed a composite sentiment indicator that proved to be more accurate in anticipating short-term stock market performance than the standard consumer confidence indicator.…”
Section: Literature Reviewmentioning
confidence: 99%